Occult lipomatosis of the nerve as part of macrodystrophia lipomatosa: illustrative case - Marek, Tomas; Amrami, Kimberly K; Spinner, Robert J (Journal of neurosurgery. Case lessons, 2023)
BACKGROUND: Macrodystrophia lipomatosa (MDL) is characterized by progressive overgrowth affecting soft tissues and bony structures and is part of lipomatous overgrowth syndromes. MDL has been associated with lipomatosis of the nerve (LN), an adipose lesion of nerve that has a pathognomonic magnetic resonance imaging (MRI) appearance as well as a mutation in the PIK3CA gene. The authors present a case of occult LN in the setting of MDL. OBSERVATIONS: A 2-year-old boy with progressive soft tissue overgrowth of his proximal right lower extremity was initially diagnosed with neurofibromatosis type 1 (NF1). At our institution, NF1 as well as other overgrowth syndromes including PTEN hamartoma tumor syndrome were excluded. He was diagnosed as having so-called MDL. Upon reinterpretation of the patient's MRI studies, short-segment LN involving the proximal sciatic nerve and part of lumbosacral plexus was identified. He underwent 2 debulking/liposuction procedures for soft tissue overgrowth. Genetic testing of tissue revealed a mutation in PIK3CA. LESSONS: Thorough clinical examination (for signs of overgrowth) as well as an MRI study of the entire neural pathway is a critical part of the diagnostic workup to evaluate for LN. The authors believe that an increasing association of LN, even when occult, will emerge that will explain many cases with marked nerve-territory overgrowth.
Keywords: macrodystrophia lipomatosa; lipofibromatous hamartoma; fibrolipomatous hamartoma; overgrowth; macrodactyly; lipomatosis of the nerve